2015
DOI: 10.1109/tps.2015.2456151
|View full text |Cite
|
Sign up to set email alerts
|

2-D Extended Fluid Model of Applied-Field Magnetoplasmadynamic Thruster With Solid and Hollow Cathodes

Abstract: In this paper, a 2-D model for simulation of an applied-field magnetoplasmadynamic (AF-MPD) thruster with solid and hollow cathodes was built using COMSOL Multiphysics. Extended fluid model was used for self-consistent simulation of discharge processes in the thruster. Ion energy balance equation was developed and added to extended fluid model. A viscously dominated steady-state fully formed gas flow was considered with argon gas used as a propellant. Electron transport properties as well as rates of electron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Model trend results were calculated using equations ( 20) and (21). The electron temperature used in equation ( 20) equals 2 eV as measured by Myers [27], and the electron number density equals ~10 20 m −3 as simulated by Li [28]. The exper imental and computational results are presented following.…”
Section: Resultsmentioning
confidence: 99%
“…Model trend results were calculated using equations ( 20) and (21). The electron temperature used in equation ( 20) equals 2 eV as measured by Myers [27], and the electron number density equals ~10 20 m −3 as simulated by Li [28]. The exper imental and computational results are presented following.…”
Section: Resultsmentioning
confidence: 99%
“…The two terms of the right side are joule heating and energy loss due to plasmachemical process, respectively [24].…”
Section: Model Descriptionmentioning
confidence: 99%
“…They obtained a set of limits to steady state plasma flow, and concluded that the Alfvén Mach number can be used to determine whether the flow will be steady or unsteady. Li et al used a more general multiphysics tool, COMSOL, to create a two-dimensional model of an AF-MPDT [117]. They used the Poisson equation to solve for the electric potential, meaning that the effects of plasma currents on magnetic field were not taken into account.…”
Section: Magnetohydrodynamic Modellingmentioning
confidence: 99%